Caspase-3 inhibitor inhibits enterovirus D68 production - Huo, Wenbo (J Microbiol, 2020)
Enterovirus D68 (EVD68) is an emerging pathogen that recently caused a large worldwide outbreak of severe respiratory disease in children. However, the relationship between EVD68 and host cells remains unclear. Caspases are involved in cell death, immune response, and even viral production. We found that caspase-3 was activated during EVD68 replication to induce apoptosis. Caspase-3 inhibitor (Z-DEVD-FMK) inhibited viral production, protected host cells from the cytopathic effects of EVD68 infection, and prevented EVD68 from regulating the host cell cycle at G0/G1. Meanwhile, caspase-3 activator (PAC-1) increased EVD68 production. EVD68 infection therefore activates caspase-3 for virus production. This knowledge provides a potential direction for the prevention and treatment of disease related to EVD68.